Some Remarks on Anthropocentrism and Didacticism as Exponents of the Homo–Animal Relationship (Based on Polish and Russian Phraseological Units with the Names of Selected Farm Animals)]. - Piasecka, Agata (Poznańskie Studia Slawistyczne, 2021)
The aim of the article is to show the relationship between the homo and animal spheres. The research material consists of Polish and Russian phraseological units in a broad sense (idioms, comparisons and proverbs) with zoonyms being the names of farm animals. The main emphasis was placed on the inherent – in faunal phraseology – and the closely related features of anthropocentrism and didacticism. Tracing the relationship between humans and animals clearly indicates the pejorativization of the linguistic image of fauna by a man. People like to use animal portraits to speak of the dark sides of their own world. Ascribing disabilities to representatives of fauna at the same time exposes the value of everything that is human. Parallel however, there is a phenomenon of hyperbolization of the negative portrait of a man who tries to subjugate living creatures from outside his species, guided by heartlessness, greed and selfishness. The lack of morality or culture cannot be considered animal traits, since higher feelings are characteristic of homo sapiens and constitute the foundation that distinguishes humans from the fauna world. Animals only fight for food, domination, and take care of the young. Their behavior is not due to ill will, lack of morals or culture. In the behavior of animals, their nature prevails and their innate instincts ensure their survival. Animals are not uncultivated and immoral, it is only a man who thinks of them in this way, involuntarily projecting his own world onto the animal world. There is a human interpretation of the world in animalistic phraseological units.